Effect of systemic immune inflammation index on symptom development in patients with moderate to severe carotid stenosis - As, Ahmet Kağan; Abanoz, Mustafa; Ozyazicioglu, Ahmet (Journal of Surgery and Medicine, 2022)
Background/Aim: Recent studies have shown that various inflammatory parameters obtained from routine blood tests can be used in the diagnosis and follow-up of cardiovascular diseases. Stroke is the second most common cause of death in the world. In this study, we aimed to investigate the role of systemic immune inflammation index (SII) value in predicting symptom development in patients with moderate to severe carotid artery stenosis (CAS). Methods: Patients between the ages of 41 and 94 with moderate to severe CAS who were followed up and treated electively in our clinic between October 01, 2016 and October 31, 2021 were included in this retrospective observational cohort study. A total of 314 consecutive patients were included in the study. The patients were divided into two groups as asymptomatic (Group 1) and symptomatic group (Group 2). Results: There were 245 and 69 patients in Groups 1 and 2, respectively. The median ages of patients in Groups 1 and 2 were 62 (41-86) years and 69 (49-94) years, respectively (P<0.001). In multivariate analysis, advanced age (OR: 1.692 CI 95%: 1.150-2.398 P=0.012), hypertension (OR: 1.114, CI 95%: 1.080-1.866, P=0.036) and SII (OR: 1.954, CI 95%: 1.090-2.942, P<0.001) values were determined as independent predictors of symptom development in patients with moderate-serious carotis artery stenosis. There was no statistically significant difference between the groups in terms of body mass index, gender, smoking, diabetes mellitus and chronic obstructive pulmonary disease rates (P>0.05 for all). Conclusion: In this current study we demonstrated that high SII value detected in asymptomatic patients with stenosis of 50% or more in the carotid arteries may be a useful marker to predict symptom development.